Factors Associated with Types and Intensity of Postoperative Pain following Gynecological Laparoscopic Surgery: A Cross-Sectional Study. (13th September 2017) - Hsien, Chia-Fen; Wang, Chiu-Lin; Long, Cheng-Yu; Chen, Yung-Hung; Lee, Winter Yu-Ning; Chen, Shih-Chin; Lin, Kun-Ling; Jeng, Cherng-Jye; Tsai, Eing-Mei; Tang, Feng-Hsiang
Abstract : Objective . To evaluate influences of various factors on the types and intensity of postoperative pain following gynecologic laparoscopic surgery. Study Design . Cross-sectional questionnaire and chart review . Results . A total of 84 questionnaires were distributed and returned. The types of postlaparoscopic pain are different in multiparous women and nulliparous ones (71.43% surgical wound pain versus 63.64% nonsurgical wound pain, p = 0.0033 ) and those with striae gravidarum and without striae gravidarum (93.94% surgical wound pain versus 52.94% nonsurgical wound pain, p < 0.0001 ). On postoperative day 1, the average VAS score is higher in nonsurgical wound pain than in surgical wound pain (5.62 ± 1.50 versus 3.51 ± 1.68, p < 0.0001 ). The CO2 removal procedure has a significant negative correlation with the VAS of nonsurgical wound pain (coefficient: - 0.4339, p = 0.0187 ). Conclusion. Our study suggests that women with abdominal rigidity (nulliparous, no striae gravidarum) experience mainly nonsurgical wound pain, while women with abdominal wall laxity mostly experience surgical wound pain. The VAS score of nonsurgical wound pain is greater than surgical wound pain on postoperative day 1. The CO2 removal procedure has negative correlation to the VAS score of nonsurgical wound pain on postoperative day 1.